2015
DOI: 10.1186/s40880-015-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends and age distribution of colorectal cancer by subsite in Guangzhou, 2000–2011

Abstract: IntroductionColorectal cancer (CRC) is the third most common cancer in China. The incidence of CRC has been increasing in recent years. The aim of this study was to explore the incidence trends and the age distribution of CRC by subsite in Guangzhou between 2000 and 2011.MethodsA total of 22,432 incident cases of CRC between 2000 and 2011 from Guangzhou Cancer Registry were identified. Crude incidence and age-standardized rates (ASRs), using the Segi’s world standard population, were calculated for CRC and CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
(15 reference statements)
2
43
2
Order By: Relevance
“…Our results are consistent with those observed in China and Africa, where the most affected site is the rectum and the least reached one is proximal colon [40,47,64]. This is not the case in developed countries as in the USA and Canada, where the most affected site is the proximal colon followed by the rectum [5,48,50,60,65].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with those observed in China and Africa, where the most affected site is the rectum and the least reached one is proximal colon [40,47,64]. This is not the case in developed countries as in the USA and Canada, where the most affected site is the proximal colon followed by the rectum [5,48,50,60,65].…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast with Australia, for example, where examined trends in national incidence rates for CRC demonstrated that rates in people under age 40 years have been rising for the last two decades (Young et al, 2015) Different mechanisms are thought to be operating in the development of colon and rectal cancer (Robsahm et al, 2013) Obesity is linked significantly to adipose tissue dysfunction and to alteration of adipokines in blood; in particular, obesity-induced inflammation is thought to be an important link between obesity and colon cancer (Janakiram andRao, 2014 Joshi andLee, 2014). However, the ratios of colon to rectum cancer did not appear to demonstrate any clear shift over time in the present study, in contrast to the situation in Japan which has seen a marked predominance of colon in more recent years (Long et al, 2010), In China also, the percentage of colon cancer in all CRCs increased significantly, especially in the descending colon and sigmoid colon (Zhou et al, 2015). A proximal shift of colon cancers has also been demonstrated in Turkey for females, but not for males (Seydaoğlu et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…In China, age-specific rates of colorectal remained relatively stable in one study (Zhou et al, 2015) and in Japan, colorectum and lung (males), showed a pattern of increasing incidence and mortality rates until the mid-1990s, stabilizing or decreasing thereafter (Katanoda et al, 2013). Thus there are considerable differences across Asian countries.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have identified the characteristic of earlier onset age in CRC patients [3]. Usually, surgical resection provides curative possibility for early stage patients, while for advanced CRC, oxaliplatin plus 5-fluorouracil and leucovorin (FOLFOX) are recommended [4].…”
Section: Introductionmentioning
confidence: 99%